1997
DOI: 10.1183/09031936.97.10102204
|View full text |Cite
|
Sign up to set email alerts
|

Ion transport in cultured pig tracheal submucosal gland acinar cells studied by X-ray microanalysis

Abstract: The submucosal glands of the airway may contribute more to the airway fluid than the surface epithelium. The cellular mechanisms underlying the regulation of electrolyte and water transport in airway submucosal glands are, however, still poorly understood. Therefore, we attempted to establish a cell culture system to facilitate study of this regulation.Acinar cells were isolated by enzymatic disaggregation from pig tracheal submucosal tissue and cultured on a plastic substrate coated with human placental colla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

1999
1999
1999
1999

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 25 publications
1
2
0
Order By: Relevance
“…The observation in this study that [Ca 2+ ] i clearly increased after ionomycin addition indicates that a Ca 2+ -activated pathway of Cl ± secretion exists in the cultured cells. Cl ± secretion in cell cultures caused by the b-adrenergic agonist isoproterenol has previously been demonstrated [16]. YAMAYA et al [24] also showed that isoproterenol induced Cl ± secretion in primary culture of human tracheobronchial gland cells, which is in line with the present results because isoproterenol is presumed to act via cAMP as an intracellular messenger.…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…The observation in this study that [Ca 2+ ] i clearly increased after ionomycin addition indicates that a Ca 2+ -activated pathway of Cl ± secretion exists in the cultured cells. Cl ± secretion in cell cultures caused by the b-adrenergic agonist isoproterenol has previously been demonstrated [16]. YAMAYA et al [24] also showed that isoproterenol induced Cl ± secretion in primary culture of human tracheobronchial gland cells, which is in line with the present results because isoproterenol is presumed to act via cAMP as an intracellular messenger.…”
Section: Discussionsupporting
confidence: 81%
“…Acinar cells were isolated and cultured as previously described [16]. Briefly, submucosal tissue was collected after the surface epithelium was removed by sharp dissection, then digested for 2 h at 378C in digesting medium containing 20 mM HEPES, type IV collagenase (500 U .…”
Section: Cell Culturementioning
confidence: 99%
“…There is growing interest in the use of cultured cells as experimental models to investigate elemental composition under different physiological and experimental conditions using X‐ray microanalysis ( Wroblewski & Wroblewski, 1993; Warley, 1994; Roomans et al ., 1996 ). Different methods have been developed and various conditions have been used to grow and prepare cultured cells for X‐ray microanalytical studies using electron probe microanalysis ( Abraham et al ., 1985 ), scanning electron microscopy (SEM) ( Zierold & Schäffer, 1988; Hall et al ., 1992 ; von Euler et al ., 1993 ; Borgmann et al ., 1994 ) and scanning transmission electron microscopy (STEM) ( James‐Kracke et al ., 1980 ; Buja et al ., 1985 ; Zierold & Schäffer, 1988; Warley et al ., 1994 ; Hongpaisan et al ., 1996 ; Zhang & Roomans, 1997a). These procedures, however, have been developed fundamentally for cells growing as monolayers on filmed grids, and the cells have generally been analysed as whole mounts and only occasionally as thin cryosections ( Buja et al ., 1985 ; Warley et al ., 1994 ).…”
Section: Introductionmentioning
confidence: 99%